SISTEM PENDETEKSI KEBOCORAN GAS LPG MENGGUNAKAN SENSOR MQ-2 BERBASIS ANDROID DAN ARDUINO - Asep Deden Rahmat S (JURNAL ILMIAH BETRIK, 2023)
Making an LPG gas leak detection system, where the detection component uses the MQ-2 gas sensor which is widely produced and widely circulated in the market, where the controller and data processing system uses an Arduino Uno-based microcontroller, besides that this system is also able to convey notifications or information to the user system smartphone, where the system displays high gas data detected by the hardware. In this study, the object of this research is the LPG gas system placed in a residential house, where the system is developed and developed using the extreme programming system development method with the implementation sequence starting from: Analysis and definition, system design, system implementation and testing. While data collection is done by observing and studying the literature, then for system modeling using UML modeling or Unified modeling language using the JAVA programming language. So that in the end an early detection system of LPG gas leaks is produced which is applied to residential homes, the advantages of which are to provide a sense of security for those who use LPG for personal needs.